Factors influencing outcomes of older children with medulloblastoma over 15 years in Peru, a resource‐limited setting. Issue 10 (20th May 2022) - Diaz‐Coronado, Rosdali Y.; Reinecke, James Brandon; Stanek, Joseph R.; Finlay, Jonathan L.; Hernández Broncano, Eddy; Chávez Paredes, Sharon; Tunque, Yesenia Miranda; Heredia Zelaya, Adela; Casavilca Zambrano, Sandro; García‐Corrochano Medina, Pamela; Ojeda Medina, Luis; Orrego Puelles, Enrique; et al.
Abstract: Background: Medulloblastoma is the most common malignant brain tumor in children. While survival has improved in high‐income countries (HIC), the outcomes for patients in low‐to‐middle‐income countries (LMIC) are unclear. Therefore, we sought to determine the survival of children with medulloblastoma at the Instituto Nacional de Enfermedades Neoplasicas (INEN) between 1997 and 2013 in Peru. Methods: Between 1997 and 2013, data from 103 children older than 3 years with medulloblastoma were analyzed. Fourteen patients were excluded. The patients were split into two distinct cohorts, 1997–2008 and 2009–2013, corresponding with chemotherapy regimen changes. Event‐free (EFS) and overall survival (OS) were calculated using the Kaplan–Meier method, whereas prognostic factors were determined by univariate analysis (log‐rank test). Results: Eighty‐nine patients were included; median age was 8.1 years (range: 3–13.9 years). The 5‐year OS was 62% (95% CI: 53%–74%), while EFS was 57% (95% CI: 48%–69%). The variables adversely affecting survival were anaplastic histology (compared to desmoplastic; OS: HR = 3.4, p  = .03), metastasis (OS: HR = 3.5, p  = .01; EFS: HR = 4.3, p  = .004), delay in radiation therapy of 31–60 days (compared to ≤30 days; EFS: HR = 2.1, p  = .04), and treatment 2009–2013 cohort (OS: HR = 2.2, p  = .02; EFS: HR = 2.0, p  = .03). Conclusions: Outcomes for medulloblastoma at INEN were low compared with HIC. Anaplastic subtype, metastasis at diagnosis, delay in radiation therapy, and treatment in the period 2009–2013 negatively affected the outcomes in our study. Multidisciplinary teamwork, timely delivery of treatment, and partnerships with loco‐regional groups and colleagues in HIC is likely beneficial.